Compression behavior of reconstituted clay: A study on black clay (Journal of Nepal Geological Society, 2018)
The soft and black clay found in the Kathmandu Valley is locally known as Kalomato which is highly compressible and weak. The Kalomato from the Khasibazaar is taken as study material. Experimental study is carried out on undisturbed, remoulded and reconstituted soil samples to determine the compression  behavior. The study revealed that the undisturbed soil sample has the highest compression  index among all samples while the remolded sample has the lowest compression index. The reconstituted soil sample using cement shows that the compression index increases with the increase in cement content while decrease with the increase in curing time. When cement content increases to 15%, the load required to compress the soil to the equal void ratio also increases to almost three times of the undisturbed soil and seven times of the remoulded soil. Therefore, reconstitution of soil using cement is found as effective method for improvement of compression  behaviour. This study also has established graphical interrelations between the compression index, swelling index and the cement content which can be used in the study of Kalomato.